2013
DOI: 10.17795/compreped-11262
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide: A Predictor for Severity Respiratory Distress Syndrome in Newborns

Abstract: Background:Respiratory distress syndrome (RDS) is considered as one of the most popular prematurity-related respiratory problems and among the most prominent reasons of deaths in preterm infants. Objectives: Brain Natriuretic Peptide (BNP) is the secret of the volume and pressure overload response of the vessels and decreases due to resistance as well as rises in systemic vessels and also in decline of pulmonary artery pressure. In the present paper, BNP is considered as a biomarker for prediction of RDS scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
1
3
0
1
Order By: Relevance
“…Our results agree with literature data on significantly lower serum leptin in patients when compared to controls (Karachaliou et al, 2006;Chaliasos et al, 2010;Shahramian et al, 2013;Elsayh et al, 2016). The low leptin in thalassaemia has been ascribed to the toxic effect of iron overload on adipose tissue (Chaliasoset al 2010).…”
Section: Behavior Of Inflammation Markers In Thalassemiasupporting
confidence: 93%
“…Our results agree with literature data on significantly lower serum leptin in patients when compared to controls (Karachaliou et al, 2006;Chaliasos et al, 2010;Shahramian et al, 2013;Elsayh et al, 2016). The low leptin in thalassaemia has been ascribed to the toxic effect of iron overload on adipose tissue (Chaliasoset al 2010).…”
Section: Behavior Of Inflammation Markers In Thalassemiasupporting
confidence: 93%
“…Shahramian et al [ 10 ] conducted a case-control study involving 65 preterm infants aged <37 weeks with Apgar score >7 as cases and 65 term infants as controls and demonstrated that serum BNP level increased among RD cases.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of preterm neonates susceptible to RDS is important since they may benefit from prophylactic surfactant administration and/or less vigorous ventilation (3,4). In this regard, Shahramian et al (5) conducted a case control study involving 65 preterm infants < 37 weeks with Apgar score > 7 as cases and 65 term infants as controls and demonstrated that serum brain natriuretic peptide (BNP) levels correlated with increased severity of RDS among cases. They suggested that BNP can be used as a prediction marker for RDS in preterm neonates.…”
Section: Dear Editormentioning
confidence: 99%
“…Therefore, levels measured soon after birth or in the cord blood may make interpretations difficult unless hour-or day-specific values of BNP and NT-pro-BNP are known. According to Shahramian et al study (5), cord blood BNP can be used to predict which preterm neonate is going to develop RDS. If it is so, neonates at risk of RDS could be monitored in a better way and receive early intervention, ultimately leading to improved survival.…”
Section: Dear Editormentioning
confidence: 99%